Urban Water Future: What Can We Learn from the Singapore Experience? - Susantono, Bambang; Li, Sarah Hui (UI Scholars Hub, 2021)
Asia and the Pacific region is a hot spot for water insecurity in the world. With water resources such as ground and surface water depleting, the demand for water consumption increases as urban population continues to grow. Meanwhile, non-revenue water (NRW) leads to inefficient water service delivery, waste of energy, drinking water contamination, loss of revenue, and increased operation costs. As the water stress continues in the region, what can cities in the region do to sustain their water future? To answer this question, this paper uses Singapore as an example and draws lessons from its urban water management experience. It finds that countries can take away from Singapore knowledge and practices, including institution autonomy paired with people-centric management, inter-agency coordination, emphasis on demand management, non-revenue water (NRW) regulation, as well as technologies and innovations. Apart from these, this paper also finds that the remaining water challenges faced by Singapore, such as climate change, energy dependence, and financial sustainability, are also shared by cities in developing Asia and Pacific countries. This paper therefore proposes solutions such as diversifying water sources and reducing NRW, increasing energy efficiency and exploring renewable energy, as well as engaging private sector investment as some of the first steps in tackling those shared challenges.